High-strength liquid ceramic tile glue and preparation method thereof

Through the combination of modified composite filler, polyurethane and modified epoxy resin, combined with hydrothermal method and chemical reaction technology, the problems of existing tile adhesives are solved, and the preparation of high-strength liquid tile adhesives are realized, which is suitable for automated construction and significantly improves the service life and safety of tiles.

CN119529743AActive Publication Date: 2025-02-28FOSHAN CHINACOW NEW MATERIAL CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411861488.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-28
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing ceramic tile glue has problems such as low bonding strength, poor water resistance, and unsuitable for automated construction during construction, resulting in insufficient service life and safety of ceramic tiles.

Method used

Modified composite fillers, polyurethane and modified epoxy resin are used as the main raw materials to generate titanium dioxide by hydrothermal method, improve the mechanical jointing and chemical bonding sites of montmorillonite, and form a cross-linked interpenetrating structure through chemical reactions to improve the adhesion and water resistance of ceramic tile glue.

Benefits of technology

It significantly improves the bonding strength and water resistance between the tiles and the substrate, enhances the comprehensive performance of tiles glue, is suitable for automated construction, extends the service life of tiles and improves the safety of use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005193311640000131
    Figure BDA0005193311640000131
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-strength liquid ceramic tile adhesive. The preparation method comprises the following steps: S1, preparing a composite filler; s2, preparation of modified polyurethane; s3, preparing modified epoxy resin; s4, preparing the liquid ceramic tile glue. According to the liquid ceramic tile adhesive, the modified composite filler, the polyurethane and the modified epoxy resin serve as main raw materials, the prepared liquid ceramic tile adhesive has excellent interface bonding performance and mechanical performance, construction convenience can be guaranteed, and meanwhile the bonding strength between a ceramic tile and a base material is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and particularly relates to a high-strength liquid tile adhesive and a preparation method thereof. Background Art

[0002] Ceramic tiles are widely used in the field of building materials. Whether it is floor or wall decoration, ceramic tiles are common building materials. Tile adhesive is a key material in the process of tile bonding, especially wall tile bonding. Its formula technology has a significant impact on the service life of ceramic tiles.

[0003] Common tile adhesives currently include dry hard mortar with cement oil, mortar mixed with construction glue, cement-based dry powder tile adhesive and tile adhesive. Dry hard mortar cement oil is a traditional tile adhesive. It has a large amount of consumables per square meter. Workers mix the ingredients on site, and the mixing ratio is adjusted according to the on-site conditions. It is not suitable for automated construction that requires a certain mix ratio. Moreover, since dry hard mortar uses medium-coarse river sand, it has poor fluidity and is also very unfavorable for automated construction. In addition, the material properties of cement oil are unstable, and problems such as poor transportation and pipe blocking may occur during machine construction. In addition, the bonding strength between dry hard mortar cement oil and tiles is low, and hollowing is prone to occur in the later stage. Mortar mixed with construction glue is also commonly used in wall tile paving in house construction. Workers also mix the materials on site, and the mix ratio is adjusted according to the on-site conditions. It is not suitable for automated construction that requires a certain mix ratio. Moreover, if machine automated construction is used, its bonding performance is difficult to guarantee during machine transfer and material transportation in long pipelines. In addition, construction glue has poor water resistance, and bricks are prone to falling off in high humidity environments in bathrooms. Single-component tile adhesive is mainly made of high molecular polymer emulsion, which is then prepared with additives such as defoaming agent, dispersant, mildew inhibitor, etc. Although it is easy to use and low cost, it generally has disadvantages such as low bonding strength, poor water resistance, anti-aging ability, and durability.

[0004] In the prior art, Chinese patent application CN113845802A discloses a waterproof coating composition, a waterproof coating and its preparation method and application. The composition contains polymer emulsion, silicate solution, filler, quartz sand, thickener, preservative, defoamer, water, and inorganic color paste; the polymer emulsion is a styrene acrylic emulsion with a glass transition temperature of 20-30°C and a solid content of 47-48wt%; the silicate solution is selected from at least one of potassium silicate solution and sodium silicate solution. The waterproof coating prepared by the waterproof coating composition provided by the invention has high bonding strength and low paint film shrinkage. However, the bonding strength of the coating to tiles is very low and cannot be used in tile adhesive for pasting tiles. Chinese patent application CN116715811A discloses a two-component tile adhesive emulsion, comprising the following components by weight: 33-110 parts of styrene, 303-410 parts of n-butyl acrylate, 105-215 parts of isooctyl acrylate, 7-11 parts of β-carboxyethyl acrylate, 14-20 parts of hydroxyethyl methacrylate, 2.4-4 parts of acrylamide, 3.5-6 parts of ethyl acetoacetate methacrylate, 0.4-0.8 parts of defoamer, 1.8-2.5 parts of bactericide, 0.6-2 parts of initiator, 4.5-13 parts of emulsifier, and 3-6 parts of curing agent. The adhesive emulsion of the invention does not contain APEO, formaldehyde, ammonia, or other pollutant emissions. The product has good stability, solves the problems of poor water resistance and low bonding strength of the two-component tile adhesive emulsion, and has the advantages of good powder compatibility, good toughness, etc. The final product has excellent performance and is green and environmentally friendly. However, the bonding strength and water resistance of the tile backing adhesive of this invention need to be further improved. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a high-strength liquid tile adhesive and a preparation method thereof. The tile adhesive has the characteristics of high bonding strength and good water resistance. After paving tiles with the high-strength liquid tile adhesive, the tiles are not prone to falling off, and the service life and safety of the tiles are improved.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing high-strength liquid tile adhesive comprises the following steps:

[0008] S1. Preparation of composite filler: adding montmorillonite to deionized water, then adding hexadecyltrimethylammonium bromide, stirring, adding ethanol, tetrabutyl titanate, and ammonia water after the stirring, carrying out hydrothermal reaction, filtering, washing, and drying after the reaction is completed to obtain a solid product; then adding the solid product to an ethanol aqueous solution, then adding vinyltrimethoxysilane, stirring and reacting, filtering, washing, and drying after the reaction is completed to obtain a composite filler;

[0009] S2, preparation of modified polyurethane: polytetrahydrofuran diol, the composite filler in step S1, diethylenetriamine, sodium lauryl sulfate, and ethyl acetate are mixed, stirred at 50-60° C. for 0.5-1 h, and then isophorone diisocyanate, pentaerythritol stearate, polyether-modified polydimethylsiloxane, and stannous octoate are added, and heated to react. After the reaction is completed, a modified polyurethane is obtained;

[0010] S3, preparation of modified epoxy resin: adding epoxy resin to a mixed solvent of ethyl acetate and xylene, then adding γ-aminopropyltriethoxysilane, 4-amino-3-fluoroallyl benzoate, and triphenylphosphine, and reacting at a constant temperature. After the reaction is completed, a modified epoxy resin is obtained;

[0011] S4, preparation of liquid tile adhesive: adding the modified epoxy resin in step S3 to the modified polyurethane in step S2, and then adding polyvinyl alcohol and azobisisobutyronitrile, stirring, and after stirring, removing ethyl acetate under reduced pressure to obtain the liquid tile adhesive.

[0012] Preferably, in step S1, the mass ratio of montmorillonite, deionized water, hexadecyltrimethylammonium bromide, ethanol, tetrabutyl titanate and ammonia water is 50-60:700-800:3-5:200-300:60-70:80-90, and the mass fraction of ammonia water is 10-15%; the temperature of the hydrothermal reaction is 110-120° C., and the time is 7-9 hours.

[0013] Preferably, the mass fraction of ethanol in the ethanol aqueous solution in step S1 is 70-80%, the mass ratio of the solid product to vinyltrimethoxysilane is 70-80:6-10; the temperature of the stirring reaction is 60-70°C, and the time is 2-3h.

[0014] In the present invention, montmorillonite is organically modified with hexadecyltrimethylammonium bromide to increase the interlayer spacing, and then titanium dioxide is generated on the montmorillonite by a hydrothermal method. On the one hand, the roughness of the montmorillonite layer is improved, the mechanical bite between the montmorillonite and the polyurethane matrix is ​​enhanced, and the strength of the tile adhesive is improved; on the other hand, the hydroxyl groups on the surface of the titanium dioxide can react with the subsequent silane coupling agent to provide more chemical bonding sites, which is conducive to the subsequent reaction.

[0015] Preferably, the mass ratio of the polytetrafuran diol, composite filler, diethylenetriamine, sodium lauryl sulfate, ethyl acetate, isophorone diisocyanate, pentaerythritol stearate, polyether modified dimethylsiloxane, and stannous octoate in step S2 is 70-80:15-20:10-15:3-5:40-50:50-60:2-3:1-2:0.5-0.8.

[0016] Preferably, the heating reaction in step S2 is carried out at a temperature of 70-80° C. and for a time of 1-2 h.

[0017] In the present invention, a composite filler is added during the preparation of polyurethane so that it is embedded in the polyurethane, thereby improving the dispersibility of the composite filler. At the same time, the added diethylenetriamine serves as a chain extender to adjust the molecular weight of the polyurethane. The added polyether-modified polydimethylsiloxane serves as a wetting agent to improve the wettability of the liquid tile adhesive so that it can be quickly spread on the tiles. The added sodium dodecyl sulfate serves as an emulsifier to improve the stability of the tile adhesive.

[0018] Preferably, the mass ratio of ethyl acetate to xylene in the mixed solution in step S3 is 80-90:10-20, and the mass ratio of the epoxy resin, γ-aminopropyltriethoxysilane, 4-amino-3-fluoroallyl benzoate, and triphenylphosphine is 100-120:10-15:5-10:1-2.

[0019] Preferably, the isothermal reaction in step S3 is carried out at a temperature of 50-60° C. and for a time of 60-90 min.

[0020] In the present invention, the epoxy resin is modified and aminotriethoxysilane and 4-amino-3-fluoroallyl benzoate are introduced into the epoxy resin by covalent bonds, which not only improves the bonding strength between the epoxy resin and the ceramic tile, but also the introduced fluorine-containing groups can improve the water resistance and weather resistance of the ceramic tile adhesive.

[0021] Preferably, the mass ratio of the modified epoxy resin, modified polyurethane, polyvinyl alcohol and azobisisobutyronitrile in step S4 is 20-30:70-80:3-4:0.3-0.5.

[0022] Preferably, the stirring temperature in step S4 is 40-50° C., the rotation speed is 100-150 r / min, and the time is 40-60 min.

[0023] In the present invention, the modified epoxy resin and the modified polyurethane are connected through a chemical reaction, so that the bonding performance of the tile adhesive is further improved. The added polyvinyl alcohol can be used as a thickener and a film-forming agent to improve the comprehensive performance of the tile adhesive.

[0024] The present invention also protects a high-strength liquid tile adhesive prepared by the method as described above.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The high-strength liquid tile adhesive provided by the present invention uses modified composite fillers, polyurethane, and modified epoxy resin as main raw materials to prepare a liquid tile adhesive having excellent interface bonding performance and mechanical properties, which can not only ensure the convenience of construction, but also significantly improve the bonding strength between tiles and substrates.

[0027] (2) The high-strength liquid tile adhesive provided by the present invention uses a hydrothermal method to in-situ generate titanium dioxide on montmorillonite. The prepared liquid tile adhesive has excellent interface bonding performance and mechanical properties, and can significantly improve the bonding strength between tiles and substrates while ensuring construction convenience. The montmorillonite is then modified using vinyl trimethoxysilane to improve the compatibility between montmorillonite and polyurethane. At the same time, double bonds are introduced into the montmorillonite, which is beneficial to the subsequent reaction. Composite fillers are added during the preparation of polyurethane and embedded in the polyurethane, thereby improving the bonding strength between the composite fillers and the polyurethane, so that the tile adhesive has good comprehensive performance.

[0028] (3) The high-strength liquid tile adhesive provided by the present invention utilizes chemical reactions to introduce aminotriethoxysilane and 4-amino-3-fluoroallyl benzoate into epoxy resin by means of covalent bonds. The silicon-oxygen bonds in aminotriethoxysilane can bond with inorganic materials in tiles, thereby improving the bonding strength between epoxy resin and tiles. Meanwhile, the fluorine-containing groups in 4-amino-3-fluoroallyl benzoate can improve the water resistance and weather resistance of the tile adhesive. Finally, the modified epoxy resin is reacted with the modified polyurethane, and the double bonds in the composite filler undergo a grafting reaction with the double bonds in 4-amino-3-fluoroallyl benzoate, so that the epoxy resin and the polyurethane form a cross-linked interpenetrating structure, thereby further improving the water resistance and bonding performance of the tile adhesive. The added polyvinyl alcohol can be used as a thickener and film-forming agent to improve the comprehensive performance of the tile adhesive. When in use, an appropriate amount of ethylenediamine can be added as a curing agent for the epoxy resin, thereby improving the bonding strength of the tile adhesive. DETAILED DESCRIPTION

[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In the present invention, the montmorillonite is sodium montmorillonite with a mesh size of 800; the molecular weight of the polytetrahydrofuran diol is 3000; the polyether-modified polydimethylsiloxane is purchased from Guangzhou Si Tu Yuan Chemical Co., Ltd., with a model of Walker VOK-1440; the brand of the epoxy resin is E-51; and the brand of the polyvinyl alcohol is PVA1799.

[0031] Example 1

[0032] A method for preparing high-strength liquid tile adhesive comprises the following steps:

[0033] S1. Preparation of composite filler: 55 g of montmorillonite was added to 750 g of deionized water, followed by addition of 4 g of hexadecyltrimethylammonium bromide, and stirred at 65° C. for 35 min. After the stirring was completed, 250 g of ethanol, 65 g of tetrabutyl titanate, and 85 g of 13% ammonia water were added, and the mixture was hydrothermally reacted at 115° C. for 8 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a solid product. Subsequently, 75 g of the solid product was added to 900 g of ethanol aqueous solution (the mass fraction of ethanol was 75%), and then 8 g of vinyltrimethoxysilane was added, and the mixture was stirred at 65° C. for 2.5 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a composite filler.

[0034] S2, preparation of modified polyurethane: 75g of polytetrahydrofuran diol, 18g of the composite filler in step S1, 13g of diethylenetriamine, 4g of sodium lauryl sulfate, and 45g of ethyl acetate were mixed, stirred at 55°C for 50min, then 55g of isophorone diisocyanate, 2.5g of pentaerythritol stearate, 1.5g of polyether-modified polydimethylsiloxane, and 0.7g of stannous octoate were added, and the mixture was reacted at 75°C for 1.5h. After the reaction was completed, a modified polyurethane was obtained;

[0035] S3, preparation of modified epoxy resin: 110g epoxy resin was added to a mixed solvent of ethyl acetate and xylene (the mass ratio of ethyl acetate to xylene was 85:15), followed by adding 13g γ-aminopropyltriethoxysilane, 8g 4-amino-3-fluoroallyl benzoate, and 1.5g triphenylphosphine, and the mixture was reacted at a constant temperature of 55°C for 80min. After the reaction was completed, a modified epoxy resin was obtained;

[0036] S4, preparation of liquid tile adhesive: add 25g of modified epoxy resin in step S3 to 75g of modified polyurethane in step S2, then add 3.5g of polyvinyl alcohol and 0.4g of azobisisobutyronitrile, stir at 45°C for 50min, and after stirring, remove ethyl acetate under reduced pressure at 13kPa to obtain the liquid tile adhesive.

[0037] Example 2

[0038] A method for preparing high-strength liquid tile adhesive comprises the following steps:

[0039] S1. Preparation of composite filler: 55 g of montmorillonite was added to 750 g of deionized water, followed by 3-5 g of hexadecyltrimethylammonium bromide, and stirred at 65° C. for 35 min. After stirring, 220 g of ethanol, 63 g of tetrabutyl titanate, and 88 g of 12% ammonia water were added, and the mixture was hydrothermally reacted at 115° C. for 8 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a solid product. Subsequently, 73 g of the solid product was added to 900 g of ethanol aqueous solution (the mass fraction of ethanol was 75%), followed by 7 g of vinyltrimethoxysilane, and the mixture was stirred at 65° C. for 2.5 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a composite filler.

[0040] S2, preparation of modified polyurethane: 73g of polytetrahydrofuran diol, 17g of the composite filler in step S1, 12g of diethylenetriamine, 4g of sodium lauryl sulfate, and 45g of ethyl acetate were mixed, stirred at 55°C for 40min, then 53g of isophorone diisocyanate, 2.5g of pentaerythritol stearate, 1.5g of polyether-modified polydimethylsiloxane, and 0.6g of stannous octoate were added, and the mixture was reacted at 75°C for 1.5h. After the reaction was completed, a modified polyurethane was obtained;

[0041] S3, preparation of modified epoxy resin: 110g epoxy resin was added to a mixed solvent of ethyl acetate and xylene (the mass ratio of ethyl acetate to xylene was 85:15), followed by adding 12g γ-aminopropyltriethoxysilane, 7g 4-amino-3-fluoroallyl benzoate, and 1.5g triphenylphosphine, and the mixture was reacted at a constant temperature of 55°C for 70min. After the reaction was completed, a modified epoxy resin was obtained;

[0042] S4, preparation of liquid tile adhesive: add 25g of modified epoxy resin in step S3 to 75g of modified polyurethane in step S2, then add 3.5g of polyvinyl alcohol and 0.4g of azobisisobutyronitrile, stir at 45°C for 50min, and after stirring, remove ethyl acetate under reduced pressure at 12kPa to obtain the liquid tile adhesive.

[0043] Example 3

[0044] A method for preparing high-strength liquid tile adhesive comprises the following steps:

[0045] S1. Preparation of composite filler: 50 g of montmorillonite was added to 700 g of deionized water, followed by 3 g of hexadecyltrimethylammonium bromide, and stirred at 60° C. for 40 min. After stirring, 200 g of ethanol, 60 g of tetrabutyl titanate, and 80 g of 15% ammonia water were added, and hydrothermally reacted at 110° C. for 9 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a solid product. Subsequently, 70 g of the solid product was added to 900 g of ethanol aqueous solution (the mass fraction of ethanol was 70%), followed by 6 g of vinyltrimethoxysilane, and stirred at 60° C. for 3 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a composite filler.

[0046] S2, preparation of modified polyurethane: 70g of polytetrahydrofuran diol, 15g of the composite filler in step S1, 10g of diethylenetriamine, 3g of sodium lauryl sulfate, and 40g of ethyl acetate were mixed, stirred at 50°C for 1h, then 50g of isophorone diisocyanate, 2g of pentaerythritol stearate, 1g of polyether-modified polydimethylsiloxane, and 0.5g of stannous octoate were added, and the mixture was reacted at 70°C for 2h. After the reaction was completed, a modified polyurethane was obtained;

[0047] S3, preparation of modified epoxy resin: 100g epoxy resin was added to a mixed solvent of ethyl acetate and xylene (the mass ratio of ethyl acetate to xylene was 90:10), followed by adding 10g γ-aminopropyltriethoxysilane, 5g 4-amino-3-fluoroallyl benzoate, and 1g triphenylphosphine, and the mixture was reacted at a constant temperature of 50°C for 90min. After the reaction was completed, a modified epoxy resin was obtained;

[0048] S4, preparation of liquid tile adhesive: add 20g of modified epoxy resin in step S3 to 70g of modified polyurethane in step S2, then add 3g of polyvinyl alcohol and 0.3g of azobisisobutyronitrile, stir at 40°C for 60min, and after stirring, remove ethyl acetate under reduced pressure at 10kPa to obtain the liquid tile adhesive.

[0049] Example 4

[0050] A method for preparing high-strength liquid tile adhesive comprises the following steps:

[0051] S1. Preparation of composite filler: 60 g of montmorillonite was added to 800 g of deionized water, followed by 5 g of hexadecyltrimethylammonium bromide, and stirred at 70° C. for 30 min. After stirring, 300 g of ethanol, 70 g of tetrabutyl titanate, and 90 g of 10% ammonia water were added, and hydrothermally reacted at 120° C. for 7 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a solid product. Subsequently, 80 g of the solid product was added to 900 g of ethanol aqueous solution (the mass fraction of ethanol was 80%), followed by 10 g of vinyltrimethoxysilane, and stirred at 70° C. for 2 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a composite filler.

[0052] S2, preparation of modified polyurethane: 80g of polytetrahydrofuran diol, 20g of the composite filler in step S1, 15g of diethylenetriamine, 5g of sodium lauryl sulfate, and 50g of ethyl acetate were mixed, stirred at 60°C for 0.5h, then 60g of isophorone diisocyanate, 3g of pentaerythritol stearate, 2g of polyether-modified polydimethylsiloxane, and 0.8g of stannous octoate were added, and the mixture was reacted at 80°C for 1h. After the reaction was completed, a modified polyurethane was obtained;

[0053] S3, preparation of modified epoxy resin: 120g epoxy resin was added to a mixed solvent of ethyl acetate and xylene (the mass ratio of ethyl acetate to xylene was 80:20), followed by adding 15g γ-aminopropyltriethoxysilane, 10g 4-amino-3-fluoroallyl benzoate, and 2g triphenylphosphine, and the mixture was reacted at a constant temperature of 60°C for 60min. After the reaction was completed, a modified epoxy resin was obtained;

[0054] S4, preparation of liquid tile adhesive: add 30g of modified epoxy resin in step S3 to 80g of modified polyurethane in step S2, then add 4g of polyvinyl alcohol and 0.5g of azobisisobutyronitrile, stir at 50°C for 40min, and after stirring, remove ethyl acetate under reduced pressure at 15kPa to obtain the liquid tile adhesive.

[0055] Comparative Example 1

[0056] A method for preparing high-strength liquid tile adhesive comprises the following steps:

[0057] S1. Preparation of composite filler: 55 g of montmorillonite was added into 750 g of deionized water, followed by 4 g of hexadecyltrimethylammonium bromide, and stirred at 65° C. for 35 min. After the stirring was completed, modified montmorillonite was obtained;

[0058] S2, preparation of modified polyurethane: 75g of polytetrahydrofuran diol, 18g of modified montmorillonite in step S1, 13g of diethylenetriamine, 4g of sodium lauryl sulfate, and 45g of ethyl acetate were mixed, stirred at 55°C for 50min, then 55g of isophorone diisocyanate, 2.5g of pentaerythritol stearate, 1.5g of polyether-modified polydimethylsiloxane, and 0.7g of stannous octoate were added, and the mixture was reacted at 75°C for 1.5h. After the reaction was completed, a modified polyurethane was obtained;

[0059] S3, preparation of modified epoxy resin: 110g epoxy resin was added to a mixed solvent of ethyl acetate and xylene (the mass ratio of ethyl acetate to xylene was 85:15), followed by adding 13g γ-aminopropyltriethoxysilane, 8g 4-amino-3-fluoroallyl benzoate, and 1.5g triphenylphosphine, and the mixture was reacted at a constant temperature of 55°C for 80min. After the reaction was completed, a modified epoxy resin was obtained;

[0060] S4, preparation of liquid tile adhesive: add 25g of modified epoxy resin in step S3 to 75g of modified polyurethane in step S2, then add 3.5g of polyvinyl alcohol and 0.4g of azobisisobutyronitrile, stir at 45°C for 50min, and after stirring, remove ethyl acetate under reduced pressure at 13kPa to obtain the liquid tile adhesive.

[0061] Compared with Example 1, in this comparative example, the montmorillonite was not modified with titanium dioxide and vinyltrimethoxysilane.

[0062] Comparative Example 2

[0063] A method for preparing high-strength liquid tile adhesive comprises the following steps:

[0064] S1. Preparation of composite filler: 55 g of montmorillonite was added to 750 g of deionized water, followed by addition of 4 g of hexadecyltrimethylammonium bromide, and stirred at 65° C. for 35 min. After the stirring was completed, 250 g of ethanol, 65 g of tetrabutyl titanate, and 85 g of 13% ammonia water were added, and the mixture was hydrothermally reacted at 115° C. for 8 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a solid product. Subsequently, 75 g of the solid product was added to 900 g of ethanol aqueous solution (the mass fraction of ethanol was 75%), and then 8 g of vinyltrimethoxysilane was added, and the mixture was stirred at 65° C. for 2.5 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a composite filler.

[0065] S2, preparation of modified polyurethane: 75g of polytetrahydrofuran diol, 18g of the composite filler in step S1, 13g of diethylenetriamine, 4g of sodium lauryl sulfate, and 45g of ethyl acetate were mixed, stirred at 55°C for 50min, then 55g of isophorone diisocyanate, 2.5g of pentaerythritol stearate, 1.5g of polyether-modified polydimethylsiloxane, and 0.7g of stannous octoate were added, and the mixture was reacted at 75°C for 1.5h. After the reaction was completed, a modified polyurethane was obtained;

[0066] S3, preparation of liquid tile adhesive: add 25g epoxy resin to 75g modified polyurethane in step S2, then add 3.5g polyvinyl alcohol and 0.4g azobisisobutyronitrile, stir at 45°C for 50min, and after stirring, remove ethyl acetate under reduced pressure at 13kPa to obtain the liquid tile adhesive.

[0067] Compared with Example 1, the epoxy resin was not modified in this comparative example.

[0068] Comparative Example 3

[0069] A method for preparing high-strength liquid tile adhesive comprises the following steps:

[0070] S1. Preparation of composite filler: 55 g of montmorillonite was added into 750 g of deionized water, followed by 4 g of hexadecyltrimethylammonium bromide, and stirred at 65° C. for 35 min. After the stirring was completed, modified montmorillonite was obtained;

[0071] S2, preparation of modified polyurethane: 75g of polytetrahydrofuran diol, 18g of modified montmorillonite in step S1, 13g of diethylenetriamine, 4g of sodium lauryl sulfate, and 45g of ethyl acetate were mixed, stirred at 55°C for 50min, then 55g of isophorone diisocyanate, 2.5g of pentaerythritol stearate, 1.5g of polyether-modified polydimethylsiloxane, and 0.7g of stannous octoate were added, and the mixture was reacted at 75°C for 1.5h. After the reaction was completed, a modified polyurethane was obtained;

[0072] S3, preparation of liquid tile adhesive: add 25g epoxy resin to 75g modified polyurethane in step S2, then add 3.5g polyvinyl alcohol and 0.4g azobisisobutyronitrile, stir at 45°C for 50min, and after stirring, remove ethyl acetate under reduced pressure at 13kPa to obtain the liquid tile adhesive.

[0073] Compared with Example 1, in this comparative example, the montmorillonite was not modified with titanium dioxide and vinyltrimethoxysilane, and the epoxy resin was not modified.

[0074] The high-strength liquid tile adhesive in Examples 1-4 and Comparative Examples 1-3 was tested for its performance in accordance with the national building materials industry standard JC / T547-2017 "Ceramic Wall and Floor Tile Adhesives". When used, 10% of ethylenediamine by mass of the liquid tile adhesive was added and mixed evenly. The results are shown in Table 1.

[0075] Table 1 Test results of tile adhesive performance in different groups

[0076]

[0077] It can be seen from Table 1 above that the liquid tile adhesive prepared by the present invention has excellent bonding strength, as well as good water resistance and weather resistance, and has good application prospects.

[0078] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-strength liquid tile adhesive, characterized in that: The following steps are involved: S1. Add montmorillonite to deionized water, then add hexadecyltrimethylammonium bromide, stir, add ethanol, tetrabutyl titanate, and ammonia water after stirring, carry out hydrothermal reaction, filter, wash, and dry after the reaction to obtain a solid product; then add the solid product to ethanol aqueous solution, then add vinyltrimethoxysilane, stir and react, filter, wash, and dry after the reaction to obtain a composite filler; S2, polytetrahydrofuran diol, the composite filler in step S1, diethylenetriamine, sodium lauryl sulfate, and ethyl acetate are mixed, and stirred at 50-60° C. for 0.5-1 h, and then isophorone diisocyanate, pentaerythritol stearate, polyether-modified polydimethylsiloxane, and stannous octoate are added, and heated to react. After the reaction is completed, a modified polyurethane is obtained; S3, adding the epoxy resin to a mixed solvent of ethyl acetate and xylene, and then adding γ-aminopropyltriethoxysilane, 4-amino-3-fluoroallyl benzoate, and triphenylphosphine, and reacting at a constant temperature. After the reaction is completed, a modified epoxy resin is obtained; S4, adding the modified epoxy resin in step S3 to the modified polyurethane in step S2, and then adding polyvinyl alcohol and azobisisobutyronitrile, stirring, and removing ethyl acetate under reduced pressure after stirring to obtain the liquid tile adhesive.

2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of montmorillonite, deionized water, hexadecyltrimethylammonium bromide, ethanol, tetrabutyl titanate and ammonia water is 50-60:700-800:3-5:200-300:60-70:80-90, and the mass fraction of ammonia water is 10-15%; the temperature of the hydrothermal reaction is 110-120° C., and the time is 7-9 hours.

3. The preparation method according to claim 1, characterized in that: In step S1, the mass fraction of ethanol in the ethanol aqueous solution is 70-80%, the mass ratio of the solid product to vinyltrimethoxysilane is 70-80:6-10; the temperature of the stirring reaction is 60-70°C, and the time is 2-3h.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the polytetrafuran diol, the composite filler, diethylenetriamine, sodium lauryl sulfate, ethyl acetate, isophorone diisocyanate, pentaerythritol stearate, polyether modified dimethylsiloxane, and stannous octoate in step S2 is 70-80:15-20:10-15:3-5:40-50:50-60:2-3:1-2:0.5-0.

8.

5. The preparation method according to claim 1, characterized in that: The temperature of the heating reaction in step S2 is 70-80° C. and the time is 1-2 h.

6. The preparation method according to claim 1, characterized in that: The mass ratio of ethyl acetate to xylene in the mixed solution in step S3 is 80-90:10-20, and the mass ratio of the epoxy resin, γ-aminopropyltriethoxysilane, 4-amino-3-fluoroallyl benzoate, and triphenylphosphine is 100-120:10-15:5-10:1-2.

7. The preparation method according to claim 1, characterized in that: The isothermal reaction in step S3 is carried out at a temperature of 50-60° C. and for a time of 60-90 min.

8. The preparation method according to claim 1, characterized in that: The mass ratio of the modified epoxy resin, modified polyurethane, polyvinyl alcohol and azobisisobutyronitrile in step S4 is 20-30:70-80:3-4:0.3-0.

5.

9. The preparation method according to claim 1, characterized in that: The stirring temperature in step S4 is 30-40° C., the rotation speed is 100-150 r / min, and the time is 40-60 min.

10. A high-strength liquid tile adhesive prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Waterproof coating composition, waterproof coating and preparation method and application thereof

    CN113845802A

  • Preparation method of bi-component ceramic tile back adhesive emulsion and bi-component ceramic tile back adhesive

    CN116715811A

  • Method for preparing modified epoxide resin embedding material

    CN101117560A

  • Impact-resistant polyurethane material laid on floor tile surface and preparation method thereof

    CN106751739A

  • Grouting type polymer binder crack repairing adhesive

    CN113462337A